The Fact of Inter-Regional Cooperation on Environmental Law in Lampung, Indonesia - Muhammad Akib; FX. Sumarja; Slamet Budi Yuwono; Hieronymus Soerjatisnanta (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to analyze the regulation of inter-regional cooperation law in environmental management in Lampung Province. The findings of this research are expected to be a basis in determining the model of legal policy of interregional cooperation in the field of environmental management in Lampung Province. Thus, the implementation of regional autonomy will be protected from regional ego and sector ego, and will eventually realize the ultimate goal of regional autonomy in the field of environment that is the welfare of local communities and environmental sustainability. This research method using socio-legal approach. The practice is primarily concerned with Local Government involvement and communities in upstream-downstream relationships in watershed (DAS) management in Lampung Province. Therefore, this study, in addition to reviewing the environmental policy of the Lampung Provincial Government, also examines district and city government environmental policies, especially in environmental management involving more than one district / city. The results showed that the legal arrangement of interregional cooperation in management of the environment in Lampung Province has not been specifically regulated. The basis of inter-regional cooperation is based only on the principles of regional autonomy and has not been based on the ecological characteristics and conditions in the region. Therefore, the approach still tends to be economic oriented and regional administration.The ideal concept is that the legal arrangement of cooperation inter-regional in the field of environment should be based on the principle of ecoregion.